Antiproliferative Effect of Antioxidative Free and Bound Phenolics from Andrographis serpyllifolia - Jayaram, Smitha; Dharmesh, Shylaja M. (Free Radicals and Antioxidants)
Background: Andrographis serpyllifolia, used as a medicinal plant in traditional practices in India, where in cancer patients are treated using the leaves of A. serpyllifolia. The crude extracts of A. serpyllifolia not only contain a wide variety of phenolic compounds but also show an excellent antioxidant activity. Therefore, this plant might be a good candidate for further development for its antioxidant remedies. However, the biological activities of the phenolic extracts of A. serpyllifolia on cancer have not been studied to date. Objective: To investigate the antioxidant and antiproliferative properties of the phenolics of A. serpyllifolia. Materials and methods: Free and (ASFP) and bound (ASBP) phenolics of A. serpyllifolia were isolated and determined antioxidant and antiproliferative abilities that are required for anticancer properties. Results: Individual phenolic constituents present in each of these fractions and their precise contribution to both antioxidant and antiproliferative activities were determined to justify the traditionally observed result of anticancer properties. Treatment of HeLa cells with ASFP and ASBP showed antiproliferative activity with increased malondialdehyde (MDA) as well as decreased levels of reduced glutathione (GSH). The present experimental data suggest that components within the ASFP may have inherent properties that suppress cancer cell proliferation. The phenolic fractions were also screened for their potential antioxidant activities using DPPH, reducing power, DNA protection, inhibition of lipid peroxidation and protein carbonyls model systems. ASFP exhibited highest antioxidant activity in all the model systems employed to study antioxidant activity. The positive correlation between polyphenolic content of A. serpyllifolia to its antioxidant activity was seen. Conclusion: Potent antiproliferative and DNA protective activity of ASFP and ASBP may contribute significantly against cancer pathogenesis.
Keywords: Antioxidant; Antiproliferative; Glutathione; Malondialdehyde; Phenolic fractions